2020
DOI: 10.21203/rs.3.rs-30347/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anxiety and Depression Symptoms of Patients in Fangcang Shelter Hospital During the COVID-19 Outbreak in China: a Web-Based Cross-Sectional Study

Abstract: Background The COVID-19 pandemic is a major health crisis has led to adverse mental health consequences in the general public, medical staff, and individual in self isolation. In order to stop transmission of the virus and save lives, Fangcang shelter hospitals were developed and used for the first time in China. However, there is no research on mental health problems in Fangcang shelter hospitals patients during the COVID-19 outbreak. The aim of this study was to survey the prevalence and major influencing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 39 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…For example, Ebola, SARS, MERS, novel influenza A, equine influenza outbreak seemed to be associated with higher levels of depression [4,6,157]. In line with previous epidemics, the COVID-19 pandemic showed a similar effect on depression [212,222,223,272,304]. In particular, quarantine and social isolation, but also the strict prevention and control requirements, and the patients' lack of communication with the outside world, were associated with higher rates of psychological depressive symptoms [78,185,187,214,216,223,245,251,321,327].…”
Section: Results For Stresssupporting
confidence: 63%
See 3 more Smart Citations
“…For example, Ebola, SARS, MERS, novel influenza A, equine influenza outbreak seemed to be associated with higher levels of depression [4,6,157]. In line with previous epidemics, the COVID-19 pandemic showed a similar effect on depression [212,222,223,272,304]. In particular, quarantine and social isolation, but also the strict prevention and control requirements, and the patients' lack of communication with the outside world, were associated with higher rates of psychological depressive symptoms [78,185,187,214,216,223,245,251,321,327].…”
Section: Results For Stresssupporting
confidence: 63%
“…Gender: The findings showed that women had higher levels of depression than men [4,8,10,67,157,186,187,[220][221][222]225,239,242,243,247,254,255,[258][259][260]262,272,307,321,347], in line with pre-COVID-19 literature [353,354]. A prolonged exposure to domestic hostility due to quarantine worsened the symptoms [259].…”
Section: Results For Depressionmentioning
confidence: 72%
See 2 more Smart Citations
“…The total score on WHOQOL‐BREF and the scores on social‐environmental support served as the dependent and independent variables, respectively. Because gender (Campos et al., 2014; Furukawa et al., 2001; Özdin & Bayrak Özdin, 2020; J. Zhang, Li, et al., 2020), age (Asar & Hakeem, 2013; Bando et al., 2015; Yueqin Huang et al., 2019), BMI (Kelderman‐Bolk et al., 2015; Kukreti, 2015), monthly income (Campos et al., 2014; Maria et al., 2010; Yoshitake et al., 2016), and health status (Campos et al., 2014; Dai et al., 2020) might affect anxiety and QoL, they were controlled during the analysis. In addition, variance expansion factors were used to diagnose collinearity in multiple regression analyses in this study.…”
Section: Methodsmentioning
confidence: 99%